2019
DOI: 10.1123/jsr.2017-0185
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise for Individuals With Spinal Cord Injury: Systematic Review Based on the International Classification of Functioning, Disability, and Health

Abstract: Introduction: Considering the reduction of physical activity performed daily in people with spinal cord injury, it is necessary to analyze the interventions based on physical exercises in order to provide recommendations based on evidence. Objectives: To review and evaluate the literature on physical exercise interventions for individuals with SCI, based on the International Classification of Functioning, Disability and Health, as well as physiological parameters for exercise prescription. Method: A systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 48 publications
0
13
0
2
Order By: Relevance
“…A growing number of studies have shown that regular physical exercise has a positive impact on the quality of life of people with SCI [6][7][8]. Over the last decades, physical exercise has been associated with muscle functional electrical stimulation (FES) resulting as an effective rehabilitation approach [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have shown that regular physical exercise has a positive impact on the quality of life of people with SCI [6][7][8]. Over the last decades, physical exercise has been associated with muscle functional electrical stimulation (FES) resulting as an effective rehabilitation approach [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[46] Treadmill running Sciatic nerve transection and repair Better motor axon regeneration and muscle fiber reinnervation [56] Treadmill running Sciatic nerve transection and repair Enhancement of motor axon regeneration [57] Mouse Treadmill running Sciatic nerve transection and repair Enhancement of motor axon regeneration [45] Treadmill running Common fibular nerve transection and repair Enhancement of axon regeneration [47] Treadmill running Common fibular and tibial nerves were cut and repaired using a graft of the same nerve from BDNFÀ/À in Schwann cells or WT mice Enhanced axon elongation [44] Treadmill running Median nerve transection and repair Better recovery of strength, muscle mass and higher expression of neurotrophic factors [52] Rat Wheel running Unilateral sciatic nerve crush Increased nerve regeneration and high levels of BDNF [41] Mouse Wheel running Long-gap sciatic nerve injury Higher innervation ratio of muscle spindles and higher number of axons/myelin in the tube. [58] Instead, no significant difference was found between the amount of exercise executed and the recovery of muscle mass, confirming the importance of the exercise quality and intensity for nerve regeneration rather than exercise volume [57].…”
Section: The Influence Of Exercise On Peripheral Nerve Regenerationmentioning
confidence: 83%
“…This result could be due to the minor effect of upslope treadmill training on proprioceptive sensory feedback from the reinnervated muscles [57]. A recent study evaluated the effects of voluntary wheel training on mice after one week from surgery on sciatic nerve treated with an acellular conduit associated with human Sk-34 cell transplantation [58]. The results showed increased numbers of axons/myelin in the tube and the contractile function in the exercise group.…”
Section: The Influence Of Exercise On Peripheral Nerve Regenerationmentioning
confidence: 99%
“…A literatura reforça os benefícios da prática regular de AF para as PCD, tais como melhora de medidas fisiológicas (redução do estresse oxidativo e peso corporal), aptidão física (aumento da força muscular, resistência cardiorrespiratória e equilíbrio), cognição (melhora da função cognitiva global, velocidade de processamento e atenção) e fatores neuropsicológicos (aumento da autoestima e redução do estresse e depressão) 20,21,23,24 . Por isso, se faz necessário orientar sobre as recomendações de AF para os diferentes ciclos de vida.…”
Section: Discussionunclassified